Anti-Bullying Education Based On Local Wisdom Through Friendship Stories For Early Childhood - Fardlillah, Qonita; Nur Sadia (JOM, 2025)
Bullying cases are the most crucial problem in Indonesia because they disturb, hurt, and even cause problems for others. Prevention of bullying in early childhood can be done by implementing character education through storytelling methods based on local wisdom in Surabaya. The study aims to (1) determine the instillation of character values ​​and local wisdom in children, (2) analyze the application of storytelling methods with a local wisdom approach in developing anti-bullying characters in early childhood. Descriptive qualitative research was conducted on research subjects of 20 students aged 4-6 years at Aisyiyah Bustanul Athfal 12 Kindergarten Surabaya. The results of the analysis show that storytelling methods based on local wisdom can encourage the development of various skills, foster positive character values, and introduce local wisdom that needs to be preserved in children. The content of the story contains an introduction to artistic elements, values ​​of tolerance, attachment and empathy so that positive characters are formed in children. Children from an early age are strengthened with character education which is one of the efforts to prevent bullying and is closely related to local wisdom because it is hoped that later children will be able to apply character values ​​in living a life that is inseparable from the local wisdom of the surrounding community.